Safety, Tolerability, Pharmacokinetics, and Pharmacodynamics of the Oral NLRP3 Inflammasome Inhibitor ZYIL1: First‐in‐Human Phase 1 Studies (Single Ascending Dose and Multiple Ascending Dose) - Parmar, Deven V.; Kansagra, Kevinkumar A.; Momin, Taufik; Patel, Hardik B.; Jansari, Gaurav A.; Bhavsar, Jay; Shah, Chintan; Patel, Jayesh M.; Ghoghari, Ashok; Barot, Ajay; Sharma, Bhavesh; Viswanathan, Kasinath; et al. (Clinical pharmacology in drug development, 2023)
ZYIL1 is a nucleotide‐binding oligomerization domain, leucine rich repeat and pyrin domain‐containing 3 (NLRP3) inflammasome inhibitor, which prevents NLRP3‐induced apoptosis‐associated speck‐like protein containing a caspase activation and recruitment domain oligomerization, thus inhibiting NLRP3 inflammasome pathway. We investigated the safety, tolerability, pharmacokinetic, and pharmacodynamic profiles of ZYIL1 after single and multiple doses in healthy subjects. The subjects aged 18–55 years were enrolled in 2 different studies: single and multiple ascending dose. Blood/urine samples were collected at designated time points for pharmacokinetic and pharmacodynamic analysis. In the single‐ascending‐dose study, 30 subjects were enrolled (6 subjects each in 5 dose groups). One adverse event was reported during the study. ZYIL1 was well absorbed with median time to maximum plasma concentration at 1–1.5 hours. The exposures were dose proportional across the dose ranges. ZYIL1 is excreted as an unchanged form via the renal route. The mean elimination half‐life was 6–7 hours. In the multiple‐ascending‐dose study, 18 subjects were enrolled (6 subjects each in 3 dose groups). Eleven adverse events were reported by 6 subjects during the study. The accumulation index at steady state for area under the plasma concentration–time curve indicated that ZYIL1 has a marginal accumulation upon repeated dosing. Dose‐proportional exposure was observed across the dose ranges. All subjects showed >90% interleukin (IL)‐1β inhibition in all dose groups for both studies. Inhibition in IL‐1β and IL‐18 was observed throughout the 14 days of treatment in the multiple‐dose study. The safety profile, rapid absorption, marginal accumulation, and significant inhibition of IL‐1β and IL‐18 level support its development for the management of inflammatory disorders.